(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the use of propranolol as a therapeutic option for childhood hemangioma, describing the evidence found in the literature, about the advantages of this new therapy when compared to conventional therapies. Methods: This is a integrative literature review, with articles in the Virtual Health Library (VHL) and PubMed databases, in Portuguese and English, using the keywords "propranolol treatment", "propranolol", "infantile hemangioma" and “hemangioma of infancy”. Results: A total of 1876 articles were found in the literature search, in which, after applying the inclusion and exclusion criteria and the peer review, there were 18 articles to be read in full. Of the 18 articles, 1380 patients who met the inclusion criteria were included. A total of 56.5% were female and comprised the age range from 1 week of life to 9 years of age. Final considerations: Propranolol is considered an alternative therapy for the treatment of infantile hemangioma because of its high efficacy and less adverse effects.